2020
DOI: 10.1080/07391102.2020.1851305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of naphthyridine and quinoline derivatives as potential Nsp16-Nsp10 inhibitors: a pharmacoinformatics study

Abstract: This research is a recent effort to explore some new heterocyclic compounds as novel and potential nonstructural protein-16-nonstructural protein-10 (Nsp16-Nsp10) inhibitors for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) inhibition. The SARS-CoV-2 is causative agent of coronavirus disease 2019 (COVID-19) pandemic. A set of 58 molecules belongs to the naphthyridine and quinoline derivatives have been recently synthesized and considered for structure-based virtual screening against Nsp16-Ns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Tables (2)(3)(4)(5)(6) show the results of the conductivity data, IR spectroscopic, electronic spectra, magnetic moment data , metals% , CHNS and physical properties of complexes.…”
Section: -Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tables (2)(3)(4)(5)(6) show the results of the conductivity data, IR spectroscopic, electronic spectra, magnetic moment data , metals% , CHNS and physical properties of complexes.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Three spin allowed transition to observe in low spin state for Mn(II) ʋ1= 12575, 12567.31 cm-1, ʋ2= 29940.12, 29960.32 cm-1 and ʋ3= 25150.01, 25120.88 cm-1 also another four metals (divalent Iron, Cobalt, Nickel, and Copper) show three bands Table (4), these complexes exhibit six-coordinate octahedral geometry [29,30] .…”
Section: 2-electronic Spectra Of the Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Tazikeh-Lemeski et al reported the drugs raltegravir and maraviroc, to be effective against nsp 16 ( Tazikeh-Lemeski et al, 2020 ). Bilal et al discovered naphthyridine and quinoline derivatives as possible nsp16-nsp10 inhibitors ( Aldahham et al, 2020 ). However, these computational investigations have not reported our compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, visible light enabled photocatalytic generation of acyl radicals, tert-butyl hydroperoxide, and cesium carbonate. In fact, it was a technique used to form α,βepoxy ketones by the reaction of a range of styrene and benzaldehydes [14]. Therefore, using the above range as well as conjugated and nonconjugated olefins, epoxyketones were synthesized by the visible-lightdriven hydroacylations and epoxyacylations in water using methylene blue as the photo redox catalyst and persulfate as the oxidant [15].…”
Section: Introductionmentioning
confidence: 99%